The Scope of National Sovereignty Over Outer Space And The Prevention Of Environmental Hazards Arising From Its Exploration, Use, and Development - Almahameed, Mwaffaq (Journal of Ecohumanism, 2025)
This study addresses issues related to the scope of national sovereignty, including the environmental dimensions related to the use and exploration of outer space. It highlights the environmental aspects related to outer space in the light of international treaties and relevant local laws. A series of results and recommendations were reached in this study, including : The absence of an international agreement on the boundaries of airspace and outer space requires the need to adopt solutions agreed upon by the international community (international treaties) so that the issue is treated as a legal issue rather than a scientific issue, emphasizing the importance of stating the obligations of States concerning the outer space environment. The use and exploration of outer space have led to the emergence of many environmental hazards and even environmental damage, such as space pollution, including orbital debris and radiation hazards, and the growth of some commercial activities harmful to the outer space environment, including the so-called space burial.